1997
DOI: 10.1016/s1078-5884(97)80187-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial doppler microembolus detection in the identification of patients at high risk of perioperative stroke

Abstract: MES counts of greater than 50/h in the early postoperative phase of carotid endarterectomy are predictive of the development of ipsilateral focal cerebral ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
0
21
0
4
Order By: Relevance
“…[3][4][5][6] Microembolic signals (MES) detected by transcranial Doppler (TCD) are associated with an increased risk of stroke and new ischemic lesions on MR scans after CEA. [7][8][9][10][11][12] In our previous study, Ͼ50 MES per hour detected during the first postoperative hour was significantly associated with new ischemic neurological deficits. 13 At present, factors involved in the generation of MES are poorly understood.…”
Section: T He European Carotid Surgery Trial (Ecst) and Northmentioning
confidence: 80%
“…[3][4][5][6] Microembolic signals (MES) detected by transcranial Doppler (TCD) are associated with an increased risk of stroke and new ischemic lesions on MR scans after CEA. [7][8][9][10][11][12] In our previous study, Ͼ50 MES per hour detected during the first postoperative hour was significantly associated with new ischemic neurological deficits. 13 At present, factors involved in the generation of MES are poorly understood.…”
Section: T He European Carotid Surgery Trial (Ecst) and Northmentioning
confidence: 80%
“…Perioperative TCD monitoring has shown that cerebral microemboli are common in patients undergoing carotid surgery [6, 7, 8, 9, 10, 11]. Most of these emboli enter the cerebral circulation without producing any significant or permanent clinical deficit after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies, with a total of 5570 individual patients, reported stroke as an outcome along with data for TCD recording of microembolic signals (7)(8)(9)(10)13,16,(18)(19)(20)23,(27)(28)(29)(30)(31)(32)(33)(34). The sensitivity and specificity were 73.14 (95% CI 48.16 to 88.86) and 70.27 (95% CI 58.61 to 79.78)* respectively.…”
Section: Strokementioning
confidence: 99%